A novel improved SLM scheme of the PAPR reduction technology in CO-OFDM systems - 袁建国 申茜 王竟鑫 王永 林金朝 庞宇 (Optoelectronics letters, 2017)
The higher peak-to-average power ratio（PAPR） is a major shortcoming of coherent optical orthogonal frequency division multiplexing（CO-OFDM） systems. Selective mapping（SLM） technology can effectively reduce the probability of high PAPR, but it has higher computational complexity, and requires additional bandwidth to transmit the side information, which will affect the transmission efficiency of the system. In response to these shortcomings, a novel improved SLM（NI-SLM） scheme with low complexity and without side information is proposed. Simulation results show that the proposed scheme can exponentially reduce the computational complexity, and the bit error rate（BER） performance can greatly approach the original signal. What＇s more, it shows the better PAPR reduction performance.